Motivational Messages in “Hamzah” Poems by Fadwa Tuqan: Gorys Keraf's Semantic Study - Chamidah, Richayatul; Wahyudi, Jarot (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
This research discusses the study of meaning in linguistics including connotation and denotation meaning. The purpose of this research is to reveal the connotative meaning in the poem